Effect of Seed Rate on Grain Growth Rate of Wheat Under Different Spacings of Poplar Based Agroforestry - Kumar, Vipin; Tewari, Salil (Indian Journal of Agroforestry, 2020)
Present experiment was conducted with an objective of studying the effect of different seed rates and tree spacings of poplar on grain growth of wheat in agroforestry system. The results revealed that during first week after anthesis, the maximum grain growth rate was obtained under 5x 6m tree spacing, significantly higher than of 5x10, 5x8, 5x 4 and 5x2m tree spacings. During second week, grain growth rate was found significantly higher under 5 x 10 m tree spacing than all the other tree spacings. The tree spacing of 5 x 4m proved to be significantly superior to all other tree spacings during third week. The maximum grain growth rate was however observed under 5x2m tree spacing, which was significantly higher than other spacings except control during fourth week. Similar effects of increased seed rates were also recorded, as 75 kg seed rate had maximum grain growth rate during first week, 100 kg seed rate during third week and 125 kg seed rate during fourth week.